Kualitas Pelayanan dan Kepuasan Nasabah pada Produk Tabungan SABAR dalam Perspektif Ekonomi Syariah: Studi pada BMT NU Cabang Kadur Pamekasan - Putri, Yunita Astri; Khairiyah, Ismiatul (JOM, 2025)
This research focuses on customer satisfaction with the SABAR Savings product offered by BMT NU Kadur Branch, examining service quality aspects from a sharia economic perspective. This research employed a qualitative approach with descriptive-analytical methods. Data were collected through direct observation, in-depth customer interviews, and relevant documentation. These data were then analyzed qualitatively to understand customer experiences and assessments of the services provided. The research results indicate that service quality is a key factor in shaping SABAR Savings customer satisfaction. The friendliness and responsiveness of staff, ease of transaction processing, and clarity of information regarding savings mechanisms and profit sharing are considered to provide a sense of security and comfort for customers. Furthermore, the consistent application of sharia principles contributes to strengthening customer trust in BMT NU as a sharia financial institution that prioritizes the needs of its members. Theoretically, the findings of this study enrich the study of customer satisfaction in sharia microfinance institutions by emphasizing the role of sharia-based service quality. Practically, the results of this study can be used as a consideration for BMT NU Kadur Branch in improving service quality and developing sharia savings products that better meet customer needs and loyalty.